Metafizyka krytyczna Ottona Liebmanna - Kubalica, Tomasz (Folia Philosophica, 2018)
In this paper I analyse the notion of critique, its subject and scope of validity in the context of critical metaphysics of Otto Liebmann. The main argument is preceded by introductory remarks in which historical context and intellectual background of this notion are discussed. The main focus of the paper is on the standpoint of Otto Liebmann, author of curricular for neo-Kantianism "Kant und die Epigonen" (1865), and who — however usually conceived to be forerunner of neo-Kantianism — quite paradoxically takes somehow different position on metaphysics. It is different from so-called late neo-Kantianism which declared itself as opposite to metaphysics. Contrary to this, Liebmann accepted the possibility of metaphysics as a kind of crowning achievement and climax of scientific theories.